The enigmatic binary system HD 5980. Issue 1 (19th March 2019) - Hillier, D John; Koenigsberger, Gloria; Nazé, Yaël; Morrell, Nidia; Barbá, Rodolfo H; Gamen, Roberto
Abstract: The Small Magellanic Cloud multiple system HD 5980 contains a luminous blue variable (LBV) that underwent a major eruption in 1994, and whose current spectrum is that of a hydrogen-rich Wolf–Rayet (WR) star. Since the eruption, the wind mass-loss rate has been declining while wind speeds have been steadily increasing. Observations obtained in 2014 when Star A (the LBV) eclipses Star B indicate that the fitted mass-loss rate and luminosity have reached the lowest values ever determined for such spectra: M = 4.5 × 10 −5 M_ yr^-1, L = 1.7 × 10 6 L⊙ . In addition, the radius of the LBV's continuum-emitting region is similar to that derived from the eclipse light curves of the late 1970s. Hence, it appears to have attained a similar 'low' state to that of the late 1970s. While a good fit to the emission spectrum is obtained using a cmfgen model, there are discrepancies in the UV. In particular, the extent of the observed absorption profiles is ∼1000 km s −1 greater than predicted by the emission-line intensities. Further, HST UV observations obtained in 2016, when Star A is eclipsed by Star B, show unusual P Cygni profiles that are not easily explained. Surprisingly the 2016 emission-line spectrum is similar to that at the opposite eclipse obtained in 2014. The complex UV profiles are likely to arise as a consequence of the dynamics of the wind–wind collision and radiative braking, both of which will cause significant departures from spherical symmetry, and have a strong orbital phase dependence. However, other scenarios, such as intrinsically aspherical winds, cannot be ruled out.